Magnetic resonance colonography with a limited bowel preparation and automated carbon dioxide insufflation in comparison to conventional colonoscopy: Patient burden and preferences. Issue 1 (January 2015) - van der Paardt, M.P.; Boellaard, T.N.; Zijta, F.M.; Baak, L.C.; Depla, A.C.T.M.; Dekker, E.; Nederveen, A.J.; Bipat, S.; Stoker, J.
Highlights: MR colonography with a limited bowel preparation and automated carbon dioxide insufflation demonstrated less burden compared to colonoscopy. When discarding the bowel preparation, the examinations were rated equally burdensome. The majority of patients preferred MR colonography over colonoscopy for their future examination of the bowel. Abstract: Objectives: To evaluate patient burden and preferences for MR colonography with a limited bowel preparation and automated carbon dioxide insufflation in comparison to conventional colonoscopy. Methods: Symptomatic patients were consecutively recruited to undergo MR colonography with automated carbon dioxide insufflation and a limited bowel preparation followed within four weeks by colonoscopy with a standard bowel cleansing preparation. Four questionnaires regarding burden (on a five-point scale) and preferences (on a seven-point scale) were addressed after MR colonography and colonoscopy and five weeks after colonoscopy. Results: Ninety-nine patients (47 men, 52 women; mean age 62.3, SD 8.7) were included. None of the patients experienced severe or extreme burden from the MR colonography bowel preparation compared to 31.5% of the patients for the colonoscopy bowel preparation. Colonoscopy was rated more burdensome (25.6% severe or extreme burden) compared to MR colonography (5.2% severe or extreme burden) ( P < 0.0001). When discarding the bowel preparations, the examinations were rated equally burdensome ( P = 0.35). The majority of patients (61.4%) preferred MR colonography compared to colonoscopy (29.5%) immediately after the examinations and five weeks later (57.0% versus 39.5%). Conclusion: MR colonography with a limited bowel preparation and automated carbon dioxide insufflation demonstrated less burden compared to colonoscopy. The majority of patients preferred MR colonography over colonoscopy.